Implementation of intensive-extensive reading strategy to improve reading comprehension - M. Zaini Miftah (Journal on English as a Foreign Language, 2015)
The study is aimed at developing the Intensive-Extensive Reading Strategy (IERS) to improve the students’ reading comprehension. The study employed Collaborative Classroom Action Research. The subjects of the study were 32 students of the second semester of English Education Study Program of STAIN Palangka Raya in the 2010/2011 academic year. The data were gained from reading comprehension test, observation, field notes and questionnaire. The findings show that the implementation of IERS with the appropriate procedures developed can improve the students’ reading comprehension. It is indicated by the improvements of the percentage of the students achieving the score greater than or equal to C (60-69), and of the percentage of their involvement in the reading activities during the implementation of IERS in Cycles I and II. Consequently, the improvement of the students’ reading comprehension can be reached but it should follow the appropriate procedures of the implementation of IERS having been developed.